2018
DOI: 10.1093/cz/zoy028
|View full text |Cite
|
Sign up to set email alerts
|

Male mate choice in livebearing fishes: an overview

Abstract: Although the majority of studies on mate choice focus on female mate choice, there is growing recognition of the role of male mate choice too. Male mate choice is tightly linked to 2 other phenomena: female competition for males and ornamentation in females. In the current article, I review the existing literature on this in a group of fishes, Poeciliidae. In this group, male mate choice appears to be based on differences in female quality, especially female size, which is a proxy for fecundity. Some males als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 184 publications
4
29
0
Order By: Relevance
“…This shift in research interest is reflected by a number of reviews within the last decade demonstrating the prevalence of female competition and male choice (Edward & Chapman, 2011; Hare & Simmons, 2018; Rosvall, 2011; Schlupp, 2018; Stockley & Bro-Jørgensen, 2011). Importantly, these behaviors are not restricted to species where there is an a priori expectation of sex-role ‘reversal’, because male-mate choice can co-occur with female mate choice, and similarly, both sexes can show intra-sexual competition for mating opportunities.…”
Section: Survey Methodologymentioning
confidence: 99%
“…This shift in research interest is reflected by a number of reviews within the last decade demonstrating the prevalence of female competition and male choice (Edward & Chapman, 2011; Hare & Simmons, 2018; Rosvall, 2011; Schlupp, 2018; Stockley & Bro-Jørgensen, 2011). Importantly, these behaviors are not restricted to species where there is an a priori expectation of sex-role ‘reversal’, because male-mate choice can co-occur with female mate choice, and similarly, both sexes can show intra-sexual competition for mating opportunities.…”
Section: Survey Methodologymentioning
confidence: 99%
“…Male investment in sexually selected traits that deliver advantages during male-male competition for females does not preclude male mate choice (Edward andChapman 2011, Schlupp 2018). Male mate choice is sometimes analogous to conventional female choice: males choose whom to reject (e.g., Schlupp 2018). Alternatively, male choice can be more subtle, such as a male adjusting his mating effort depending on a female's quality (Bonduriansky 2001;Engqvist and Sauer 2001;Reinhold et al 2002;Nandy et al 2012;Godin and Auld 2013), and/or the size of the ejaculates he transfers (Simmons et al 2007;Kelly and Jennions 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies in the Poeciliidae do not report a significant correlation between female size and multiple paternity (Trexler, 1997;Zane et al, 1999;Neff et al, 2008;Girndt et al, 2012;Paczolt et al, 2015;Zeng et al, 2017), although a significant relationship was found in Gambusia affinis and Poecilia latipinna (Travis et al, 1990;Greene and Brown, 1991). We expected to find a positive relationship between female size and multiple paternity, as many earlier studies have shown a male preference for larger females (including the closely related P. reticulata and P. latipinna; Bisazza et al, 1989;Ptacek and Travis, 1997;Dosen and Montgomerie, 2004;Herdman et al, 2004;Hoysak and Godin, 2007;Schlupp, 2018). But this preference, usually assessed using choice-experiments in the lab, might not reflect actual mating opportunities in natural situations.…”
Section: Effect Of Female Traits On Multiple Paternitymentioning
confidence: 72%
“…Simple mathematics dictate that the larger a brood, the larger the absolute number of potential sires that can contribute to that brood (Avise and Liu, 2011): i.e., a brood of two offspring can be sired by a maximum of two fathers, while a brood of 30 offspring can be sired by a maximum of 30 different males. Several studies have furthermore shown that males prefer to mate with larger females (Bisazza et al, 1989;Ptacek and Travis, 1997;Dosen and Montgomerie, 2004;Herdman et al, 2004;Hoysak and Godin, 2007), presumably because they increase their chance of producing more offspring as these females generally carry more eggs (Schlupp, 2018). These above processes may explain the observed positive associations between female size, brood size and multiple paternity.…”
Section: Introductionmentioning
confidence: 94%